116 Management of acute neurological conditions: an e-learning course to support clinical pathways. Issue 6 (27th May 2022) - Wu, Kit; Farag, Mena; Tamborska, Arina; Mahmood, Amira; Theochari, Evangelia; Larcombe, Karen; Ellis, Cathy
Abstract : Introduction and Aim : Acute neurological problems are prevalent, accounting for 10–20% of medical admissions, but management is often challenging and require input from different teams (A&E, acute medicine, neurology). There is no standardised training for staff in the management of acute neurological conditions and existing clinical pathways for these conditions are often underutilised with variable impact on patient outcome. The use of e-learning has gained popularity in the last decade, showing that it can be as effective as conventional didacticism [Warnecke et al, 2011]. Here, we detail the development of an e-learning course on management of acute neurological conditions to support use of integrated clinical pathways and to facilitate self-directed learning. Method and Results : Using principles of People, Analysis, Content and Technology (PACT), we defined target learners, their learning needs, challenges in assimilating knowledge and the resources required. Topics were derived from three themes: acute neurological emergencies, commonly seen conditions, and 'lessons from serious incidents'. Each module lasts 10 minutes and is embedded with a pre- and post-course knowledge quiz. In collaboration with the Neurosciences Institute Programme at King's Health Partners, an academic Health Science Centre, the course will be hosted and supported by the KHP e-learning platform. Summary: This e-learning course supports the use of clinical pathways and facilitates clinicians in consoli- dating knowledge. It is flexible, highly transferable, and can be integrated into work-based learning for continuous professional development. kitwu@doctors.org.uk